Археологічна розвідка в околицях села Баговиця Кам’янець-Подільського району у 2019 році (ур. Нова ферма) - Старенький, І.О.; Болтанюк, П.А. (Сіверщина в історії України, 2020)
У статті висвітлюється інформація про нововідкрите у квітні
2019 року багатошарове поселення на північ від с. Баговиця Кам’янець-Подільського району Хмельницької області. Вдалося встановити, що пам’ятка налічує п’ять хронологічних горизонтів, а саме:
трипільська культура, ранній залізний вік, черняхівська культура, празько-корчацька культура та давньоруський час. З’ясовано,
що поселення пошкоджене «чорними археологами», в деяких місцях культурний шар повністю знищений внаслідок сільськогосподарських робіт (материкова порода залягає вже на глибині 0,25–0,3 м). Частина пам’ятки сьогодні заболочена мочарами, вода з
яких стікає у струмок Біла Криниця (права притока р. Баговиця),
на лівому березі якого й розташоване поселення. The article highlights the results of archaeological excavations at a newly
discovered settlement north of the village of Bahovitsa, Kamiianets-Podilskyi
district, Khmelnytskyi region in the New Farm (Boiarskyi Farm) tract. The
settlement was opened in April 2019 and surveyed by the Kamiianets-
Podilskyi Archaeological Expedition of the State Historical Museum-
Reserve (trial trenching was held by Ihor Starenkyi, Petro Boltaniuk, Evhenii
Levinson). It was established that the settlement is multilayered and has
five chronological horizons: Trypillian culture, early Iron Age, Cherniakhiv
culture, Prague-Korchak culture and Old Rus period of 12-13 centuries.
The settlement is located mainly on the left bank of the Bila Krynychka
Stream - the right tributary of the Bahovitsa River. In ancient times, this
area probably had a difficult terrain, as numerous ravines destroyed by
agricultural work are still visible in the area. A relatively small part of the
settlement is wetland. Most of its territory is ruined. In places, the cultural
layer is completely destroyed. In addition, there are numerous traces of
the activities of “black archaeologists”. Trypillian culture is represented by
small fragments of ceramics and flint tools. Actually, this did not allow us to
determine the stage and the local group. Several fragments of early Iron Age
pottery were also found. Unfortunately, the small size and fragmentation
of the material do not make it possible to assign it to Cherniakhiv culture
or Early Scythian times. A relatively small number of fragments of ceramic
products, which can probably be attributed to Prague-Korchak culture,
as well as single fragments of ceramics of ancient times, were also found.
At the same time, most of the material found is attributed to Cherniakhiv
culture in the chronological framework of its highest development (3 - the
first half of the 5th century). The finds are represented by fragments of
pots, bowls, jugs, pithos, a glass cup.